Consumer acceptance of dry dog food variations - Di Donfrancesco, Brizio; Koppel, Kadri; Swaney-Stueve, Marianne; Chambers, Edgar, IV (My University, 2014)
The objectives of this study were to compare the acceptance of different dry dog food products by consumers, determine consumer clusters for acceptance, and identify the characteristics of dog food that drive consumer acceptance. Eight dry dog food samples available in the US market were evaluated by pet owners. In this study, consumers evaluated overall liking, aroma, and appearance liking of the products. Consumers were also asked to predict their purchase intent, their dog’s liking, and cost of the samples. The results indicated that appearance of the sample, especially the color, influenced pet owner’s overall liking more than the aroma of the product. Overall liking clusters were not related to income, age, gender, or education, indicating that general consumer demographics do not appear to play a main role in individual consumer acceptance of dog food products.
Keywords: Appearance; Aroma; Consumer; Dog; Pet food